Analysis of Ultrahigh Apparent Mobility in Oxide Field‐Effect Transistors. Issue 7 (25th January 2019) - Chen, Changdong; Yang, Bo‐Ru; Li, Gongtan; Zhou, Hang; Huang, Bolong; Wu, Qian; Zhan, Runze; Noh, Yong‐Young; Minari, Takeo; Zhang, Shengdong; Deng, Shaozhi; Sirringhaus, Henning; et al.
Abstract: For newly developed semiconductors, obtaining high‐performance transistors and identifying carrier mobility have been hot and important issues. Here, large‐area fabrications and thorough analysis of InGaZnO transistors with enhanced current by simple encapsulations are reported. The enhancement in the drain current and on–off ratio is remarkable in the long‐channel devices (e.g., 40 times in 200 µm long transistors) but becomes much less pronounced in short‐channel devices (e.g., 2 times in 5 µm long transistors), which limits its application to the display industry. Combining gated four‐probe measurements, scanning Kelvin‐probe microscopy, secondary ion mass spectrometry, X‐ray photoelectron spectroscopy, and device simulations, it is revealed that the enhanced apparent mobility up to several tens of times is attributed to the stabilized hydrogens in the middle area forming a degenerated channel area while that near the source‐drain contacts are merely doped, which causes artifact in mobility extraction. The studies demonstrate the use of hydrogens to remarkably enhance performance of oxide transistors by inducing a new mode of device operation. Also, this study shows clearly that a thorough analysis is necessary to understand the origin of very high apparent mobilities in thin‐film transistors or field‐effect transistors with advanced semiconductors. Abstract : With simple and optimized encapsulations, InGaZnO thin‐film‐transistors (TFT) achieve significantly enhanced apparent mobility (up to 40 times) as compared with pristine TFT. To understand that, the current–voltage characteristics, capacitance–voltage relations, gated four‐probe measurement for potentials, scanning Kelvin probe microscope for surface, 2D technology computer aided design device simulations, depth‐profiling of elements, photoelectron spectroscopy for ions, density functional theory calculations, and temperature‐dependent measurements are investigated.